Pengaruh Kualitas Pelayanan Dan Harga Kopi Kenangan Metro Terhadap Loyalitas Pelanggan Dengan Kepuasan Pelanggan Sebagai Variabel Intervening (Studi Pada Mahasiswa Manajemen Angkatan 2019 Universitas Muhammadiyah Metro) - Nina Lelawati; Suwarto; Roid Azhar Aziz (Universitas Muhammadiyah Metro, 2025)
Customer loyalty is a form of customer loyalty to the company for purchasing the company's products. Customers who are loyal will of course make repeat purchases of the products they buy. The aim of this research is to find out whether there is a direct influence on service quality, price and customer satisfaction on customer loyalty among Metro City Memories Coffee consumers. This research uses a quantitative method by measuring research variables using an instrument in the form of a questionnaire given by Kopi Kenangan consumers in Metro City. The research population was all consumers of memorable coffee with samples taken using an accidental sampling technique so that the number of samples encountered during the research period was 68 people. The collected questionnaire data was then analyzed using a path analysis formula with two structural models. The research results show that there is a direct influence of service quality on satisfaction, there is a direct influence of price on satisfaction, there is a direct influence of service quality on loyalty, there is a direct influence of price on loyalty and there is a direct influence of customer satisfaction on loyalty.